Reusing resources and transforming the future through Environmental Education (Research, Society and Development, 2022)
The ecological moment needs to use all knowledge and experience for the implementation of sustainability in all the fields of social reality. Then, the actual Environmental Education should spread “Ecoeducation” related to the lack of information that involves the correct destination and use of some waste, especially domestic waste. This article had a practical and theoretical foundation in a university extension Project developed at the Universidade do Estado de Minas Gerais, João Monlevade Unit, which used Environmental Education to collect and reuse cooking oil already used in food preparation. Initially structured to be develped in person at the elementar schools of João Monlevade, Minas Gerais, the Project hat to undergo adaptations due to the changes caused by the remote classes implemented during the year 2021, because of the pandemic caused by Covid-19. The Project aimed to collect cooking oil to be reused in the manufacture of soap and other products. As it was not possible to develop actions in schools, the project team used social media to raise awareness of the correct disposal importance and reuse of cooking oil. Thus, in partnership with some agencies of the local city hall, some places called “Ecopoints” were installed to collect the oil that would be aimed for recycling. The project has been received well through the participation of the local population and demonstrated that, if properly guided, individuals can collaborate with sustainable practices, in a joint effort to consolidate socio-environmental attitudes.